Contract Farming and Food Security in Developing Economies: A Framework Model for Spillover Impact - Gouranga G. Das; Ranajoy Bhattacharya (Global Labor Organization (GLO), 2024)
Empirical literature on the effect of Contract Farming (CF) on economic development of a Less Developed Economy (LDC) is divided on the basic issue of concern for the policy makers in LDCs: should CF be encouraged, and if so, under what circumstances? Broadly, there are both intermediate (yield, price etc.) and ultimate (mainly household income and food security) benefits. However, the implication of the outcomes on welfare are not unidirectional. For instance, in most cases yield per hectare and household income of farmers increased along with rise in prices of crops. Das, Bhattacharya and Marjit (JRFM, 2023) builds a model to explore such adverse welfare impacts due to CF. This paper's focus is totally different. Also, there is no homogeneity in the sample of crops or the country of occurrence. Since most of these contracts are private in nature with a clear objective of profit maximization, the estimates could have self-section biases, which is rarely controlled for. Additionally, these are mostly in the nature of treatment/control group studies (though not RCTs). A fundamental issue is that spillover effects bias outcomes in these methods and it should be controlled for. This implies that there is virtually no empirical literature on spillover effects. Looking at it differently, these studies conclude that in the absence of spillover effects CF appears to be conditionally beneficial to LDCs. Given this background, this paper investigates: what are the nature of these conditions? To what extent do spillover effects relax them? Constructing a three-sector-four-factors general equilibrium model: agricultural with contract farming, traditional agriculture, and manufacturing, we derive the conditions under which it is conducive for low-income farmers. The objective is to prescribe a clear set of recommendations to the governments of the LDCs that are experimenting with CF on the nature of priors that they need to ensure for significantly increasing the probability of net benefit from CF.
Keywords: F22; J31; Q15; 330; Land deal; Contract Farming; Vertical Coordination; Wage gap; Self-selection Bias; Spillover; Governance